2021
DOI: 10.3390/fi13120309
|View full text |Cite
|
Sign up to set email alerts
|

DNS Firewall Based on Machine Learning

Abstract: Nowadays there are many DNS firewall solutions to prevent users accessing malicious domains. These can provide real-time protection and block illegitimate communications, contributing to the cybersecurity posture of the organizations. Most of these solutions are based on known malicious domain lists that are being constantly updated. However, in this way, it is only possible to block malicious communications for known malicious domains, leaving out many others that are malicious but have not yet been updated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The average precision value improvement by our approach over all baseline approaches is 0.051%, 0.049%, 0.019%, 0.04%, 0.034%, and 0.016% compared with LDA [2], [20][21][22][23], SVM [2,24], KNN [2,[25][26][27], LR [2,28], NB [2,29], and DT [2,30], respectively. In terms of recall, our approach obtains 0.988%.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The average precision value improvement by our approach over all baseline approaches is 0.051%, 0.049%, 0.019%, 0.04%, 0.034%, and 0.016% compared with LDA [2], [20][21][22][23], SVM [2,24], KNN [2,[25][26][27], LR [2,28], NB [2,29], and DT [2,30], respectively. In terms of recall, our approach obtains 0.988%.…”
Section: Resultsmentioning
confidence: 99%
“…After obtaining probabilities from multiple classifiers, a threshold filter is applied to the probabilities to finally determine whether the URL is malicious or not. Marques et al [2] empirically investigated the impact of three feature selection methods applied to six classification models on the performance of malicious domain name detection. They conducted experiments on the malicious domains dataset, and found that the decision trees with recursive feature elimination were more suitable for the malicious domain detection task, compared with other baseline methods.…”
Section: Machine Learning Approachesmentioning
confidence: 99%
See 3 more Smart Citations